The Role of Big Data Analytics in Supporting Decision-Making Theories in Companies - Faizah Ats Tsaniyah; Ningsih, Santika Purwaty; Cyntia, Dinda Yovita; Kusumasari, Indah Respati; Hidayat N, Rusdi (Indonesian Journal Publisher, 2025)
Advances in information technology have sparked a revolution in data processing and analysis. Big Data Analytics (BDA) plays an important role in enabling companies to make faster, more accurate, and data-driven decisions. This study adopts a qualitative research approach to explore the intersection of Big Data Analytics (BDA) and decision-making theory. Qualitative research is well suited for this purpose as it enables in-depth exploration of complex phenomena and provides rich contextual insights. Big Data Analytics (BDA) plays an important role in improving decision-making by providing accurate, timely and evidence-based insights. In the manufacturing sector, BDA is used for real-time quality monitoring and predictive maintenance. Big Data Analytics (BDA) contributes significantly to supporting decision theory by improving the quality, speed, and accuracy of the decision-making process. Companies are advised to build a technology infrastructure that supports the comprehensive implementation of BDA.